Development of Bird Diversity Supplement Book in the Limboto Lake Area Gorontalo Province - Dama, Windiawati Windi; Latjompoh, Masra; Ibrahim, Mustamin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Labuhanbatu, 2022)
The development of learning resources can be developed from the potential of the surrounding environment. Birds in Limboto lake have the potential to be used as easy and interesting learning resources because they are close to students' daily lives so that the learning process is not just learning. Supplementary books are one solution to make it easier for students to learn independently in their environment. Â This study aims to determine the validity test in developing a bird diversity supplement book in the Limboto Lake area, Gorontalo Province. This research belongs to the type of research and development research and development (R&D). Research and development procedures include preliminary studies, information gathering, supplement book design, supplement book validation, and supplement book revision. The instrument used in collecting data is a validation sheet which is analyzed using a validation formula. The results of the supplementary book validity test obtained an average value of 83.1% with a very valid category. It can be concluded that the bird diversity supplement book meets the valid criteria so that it is feasible to use